The crystal structure of 4-aminiumbiphenyl benzenesulfonate, C18H17NO3S - Shi Chengzhe; Chen Xinlei; Jin Shouwen; Chen Shiyi; Wang Daqi (Zeitschrift für Kristallographie - New Crystal Structures)
C18H17NO3S, monoclinic, Cc (no. 9), a = 32.036(3) Å, b = 7.2154(7) Å, c = 7.4283(8) Å, β = 99.943(2)∘, V = 1691.3(3) Å3, Z = 4, Rgt(F) = 0.0343, wRref(F2) = 0.0821, T = 298 K.